The Acordada mutiny and the Looting of Parián in Response to the Results of the 1828 Presidential Election Process in Mexico - Acostaviques Ortiz, Columba (2024)
The Acordada mutiny and the looting of Parián, depicted the electoral failure of 1828 and were a significant reflection of the economic, political, and social instability that Mexico had been experiencing since the promulgation of the first federal constitution four years earlier. This constitution sanctioned a diffuse and indirect electoral process as a result of a poor adaptation of the American system. In this context, the political campaign took place to elect the second president of the nation, whose candidates primarily represented the two groups united around masonic rites, and also associated with the two distinct ways of building the nation: liberals of the York rite and conservatives of the Scottish rite, along with some moderate Yorkists. The results were contested through violence leading to the occurrence of these two events that culminated in an armed confrontation, ending in a paralyzing discontent.